ANALISIS PERBEDAAN KEEFEKTIFAN KINERJA LALU LINTAS PADA RUAS JALAN LINGKAR TEMBOLAK - fivin wulandari; Eti Kurniati (Hexagon, 2024)
Mataram is a city that has a fairly rapid population growth and development rate, rapid development and growth has made the volume of vehicle use also increase both from the use of goods or services. The activities of residents living in urban areas create areas of attraction and generation areas that increase traffic demand. The ring road is usually used as a solution to reduce congestion because there is a sufficiently increased need for traffic. This can occur in the city of Mataram, resulting in congestion, but there are several roads that are very effectively used to reach the area of ??interest we are going to. To find out which road is more effective to get to the attraction area, we can use the origin-destination matrix with the origin-destination matrix method. Based on the condition of the ring road, we can conduct research related to a comparison of which 2 roads are more effective to use to get to the attraction area. The results of the calculation are for the capacitance value to get a value of 70425 pcu/hour from all the arms at the Tugu Metro Mataram roundabout. And the DS value of 0.24 indicates that the road is not saturated and the road that is effectively used is 2 arms, namely arm A and arm B based on the factors of attraction and generation